Impact of a third-year surgical apprenticeship model: Perceptions and attitudes compared with the traditional medical student clerkship experience - Reid, Christopher; Kim, D.; Mandel, J.; Smith, A.; Talamini, M.; Bansal, V. (Elsevier Inc., 2014)
Background Current literature suggests that medical students may have negative misconceptions of a surgical career partly due to the traditional hierarchical structure of the surgical clerkship. We hypothesized that a novel medical student apprenticeship would result in positive changes in perceptions of both surgeons and surgical careers. Study Design In the 2011 academic year, third-year medical students were offered a 2-week apprenticeship elective, in addition to the standard 8-week surgical clerkship. Unlike a traditional service, students apprenticed directly with participating faculty on a one-on-one basis. At the clerkship's end, students received a structured questionnaire assessing perceptions and attitudes toward surgeons and a career in surgery. Subjects responded anonymously using a 5-point Likert scale. A Wilcoxon Rank-Sum was performed comparing students who participated vs those who did not participate in the apprenticeship. Results There was a 99% survey response (105 of 106). Of those, 50 (48%) participated in the apprenticeship. Apprenticeship students were more likely to view surgeons as content (p < 0.001), well-balanced (p < 0.01), respectful (p = 0.01), and as role models (p < 0.005). Apprenticeship students were also more likely to participate in the operating room (p < 0.05) and in patient management (p < 0.05). There was no difference in an interest to pursue a surgical career between groups both before and on completion of the clerkship. Conclusions Students participating in a surgical apprenticeship had a more positive view of surgeons and the field of surgery compared with students not participating. An apprenticeship model enhances the surgical clerkship experience and improves medical student perceptions of surgery as a career. © 2014 by the American College of Surgeons Published by Elsevier Inc.